A comprehensive experimental study on the production of key platform chemicals from raw biomass. (15th November 2020) - Nis, Berna; Kaya Ozsel, Burcak
Highlights: Sorghum is a feedstock with significant potential in production of LA. Organic solvents with different polarity have a direct effect on product yield. Methanol, a polar protic solvent, can be preferable for production of xylose. Abstract: In recent years, the utilization of biomass resources in the production of industrial chemicals and fuels become more preferable when considering low cost, renewability and environmental concerns. In this study, 5-hydroxymethylfurfural and levulinic acid obtained from catalytic one-pot reaction of different feedstocks (microcrystalline cellulose, corn straw, sorghum and waste fluff) under the specified conditions (temperature, time, solvent ratio, catalyst loading) using different cosolvents (methanol, hexane, tetrahydrofuran (THF), acetone) in reaction medium. Over the Amberlyst-15 catalyst, significant increase in levulinic acid concentration was achieved using acetone as cosolvent thus 94.34 ± 5.25 mg levulinic acid was obtained from 1 g sorghum at 180 °C for 30 min. The use of polar aprotic solvents such as THF and acetone promoted further hydrolysis of raw biomass materials in reaction medium.